Risk assessment of potentially toxic element pollution in soils and rice ( Oryza sativa) in a typical area of the Yangtze River Delta - Hang, Xiaoshuai; Wang, Huoyan; Zhou, Jianmin; Ma, Chengling; Du, Changwen; Chen, Xiaoqin (Environmental pollution (1987), 2009)
Soil pollution with potentially toxic elements (PTEs) resulting from rapid industrial development has caused major concerns. Selected PTEs and their accumulation and distribution in soils and rice ( Oryza sativa) collected from Changshu, east China, were analyzed to evaluate the potential health risk to the local population. The soils were primarily contaminated with Hg, followed by Cu, Cd, Pb, and Zn. The concentrations of Pb, Hg, and Cd of 46, 32, and 1 rice samples exceeded their national maximum allowable levels in foods, respectively. Spatial distributions of total Cr, Cu, Pb, Zn, and Cd in soils shared similar geographical trends. The risk assessment of PTEs through rice consumption suggests that the concentrations of Cu, Pb, and Cd in some rice samples exceed their reference oral dose for adults and children. In general, there was no target hazard quotient value of any individual element that was greater than 1, but hazard index values for adults and children were 1.726 and 1.523, respectively. Industrial development has led to increased risk from potentially toxic elements in soils and rice.